MiR-143 and rat embryo implantation - Tian, Shi; Su, Xing; Qi, Lu; Jin, Xiao-Hua; Hu, Yi; Wang, Chun-Ling; Ma, Xu; Xia, Hong-Fei (Biochimica et biophysica acta, 2015)
To study the role of miR-143 during embryo implantation in rat. MiR-143 expression in rat early pregnancy was detected by Northern blot. The relation between miR-143 and Lifr predicted and confirmed by bioinformatics method, dual-luciferase activity assay, Western blot and immunohistochemistry. The role of miR-143 was detected by MTS, Edu and ranswell chamber assays. The expression level of miR-143 on gestation day 5-8 (g.d. 5-8) was higher than on g.d. 3-4 in uteri of pregnant rat. MiR-143 was mainly localized in the superficial stroma/primary decidual zone, luminal and glandular epithelia. The expression of miR-143 was not significantly influenced by pseudopregnancy, but the activation of delayed implantation and experimentally induced decidualization significantly promoted miR-143 expression. Over-expression of miR-143 in human endometrial stromal cells (ESCs) inhibited cell proliferation, migration and invasion. Knockdown of miR-143 promoted cell proliferation and invasion. The results of recombinant luciferase reporters showed that miR-143 could bind to the 3¢-untranslated region (UTR) of leukemia inhibitory factor receptor (Lifr) to inhibit Lifr translation. Uterine miR-143 may be involved in the successful pregnancy, especially during the process of blastocyst implantation through regulating Lifr. This study may have the potential to provide new insights into the understanding of miR-143 function during embryo implantation.